Molecular characterization of extended spectrum β-lactamase-producing Enterobacteriaceae strains isolated from a tertiary care hospital. (February 2018) - Jena, Jayanti; Debata, Nagen Kumar; Sahoo, Rajesh Kumar; Gaur, Mahendra; Subudhi, Enketeswara
Abstract: Infectious diseases caused by ESBL producing Enterobacteriaceae are an emerging problem worldwide which increases the empirical treatment failure, hospital cost, rate of morbidity and mortality. This also leads to the Hospital infection outbreak. Present study was undertaken to determine the frequency of bla TEM, bla CTX-M and bla SHV genes among Enterobacteriaceae . A total of 751 non-repeated clinical isolates of Enterobacteriaceae family were included in this study. Antibiotic susceptibility test was done and minimal inhibitory concentration (MIC) against four antibiotics was carried out. Five hundred fifteen multi drug resistant isolates were tested for ESBL by CLSI confirmatory method. Isolates showing ESBL positive by phenotypic method were screened for bla TEM, bla CTX-M and bla SHV genes by monoplex PCR. Two bla TEM and two bla CTX-M amplified products were selected randomly for sequencing. Sequencing data was submitted to NCBI data base. Of the 515 MDR isolates, 140 showed ESBL production by phenotypic method. All the ESBL producing isolates showed resistant to ceftazidime (100%). IMP, TGC and CL drugs could be preferred for the treatment of ESBL producers as these drugs showed a lower rate of resistance. bla TEM gene was the predominant (96.42%) followed by bla CTX-M (75%) and bla SHV (17.85%). All the three bla genes were occurred in 22 (17.14%) isolates. All the phenotypically confirmed ESBL producers were found contain any one of the three bla genes. It is concluded from the study that the bla TEM was predominantly found in Enterobacteriaceae and bla CTX-M gene also seemed to emerging. Highlights: ESBL producing Enterobacteriaceae isolates were collected from clinical specimens. All the isolated strains were multidrug resistance. ESBL production was determined by phenotypicaly and genotypicaly (PCR). TEM gene was predominant and CTX-M was also found in increasing.